On the United Theory of the Family of Euler-Halley Type Methods with Cubical Convergence in Banach Spaces (Journal of Computational Mathematics, 2003)
The convergence problem of the family of Euler-Halley methods is considered under the Lipschitz condition with the $L$-average, and a united convergence theory with its applications is presented.
Keywords: Operator equation; The family of Enler-Halley; Iterations; Cubical convergence.